2008
DOI: 10.1128/jb.01322-07
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Lethality, Division Defects, Membrane Involution, and Endocytosis inmreandmrdShape Mutants ofEscherichia coli

Abstract: Maintenance of rod shape in Escherichia coli requires the shape proteins MreB, MreC, MreD, MrdA (PBP2), and MrdB (RodA). How loss of the Mre proteins affects E. coli viability has been unclear. We generated Mre and Mrd depletion strains under conditions that minimize selective pressure for undefined suppressors and found their phenotypes to be very similar. Cells lacking one or more of the five proteins were fully viable and propagated as small spheres under conditions of slow mass increase but formed large no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
278
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(292 citation statements)
references
References 92 publications
12
278
2
Order By: Relevance
“…The MreBCD complex in rod-shaped bacteria localizes along the membrane, acting as a spatial organizer of various processes (7,9,(30)(31)(32)(33). In Escherichia coli, MreB (an actin-like molecule) is required to regulate phospholipid and membrane biosynthesis (31). However, MreB is missing in S. aureus and other coccal cells, whereas MreC and MreD are present (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MreBCD complex in rod-shaped bacteria localizes along the membrane, acting as a spatial organizer of various processes (7,9,(30)(31)(32)(33). In Escherichia coli, MreB (an actin-like molecule) is required to regulate phospholipid and membrane biosynthesis (31). However, MreB is missing in S. aureus and other coccal cells, whereas MreC and MreD are present (9).…”
Section: Resultsmentioning
confidence: 99%
“…PlsY and/or CdsA seemed unlikely candidates as organizers of the patterned distribution, as did FtsZ, despite its link to the localization of phospholipid synthases (29). The MreBCD complex in rod-shaped bacteria localizes along the membrane, acting as a spatial organizer of various processes (7,9,(30)(31)(32)(33). In Escherichia coli, MreB (an actin-like molecule) is required to regulate phospholipid and membrane biosynthesis (31).…”
Section: Resultsmentioning
confidence: 99%
“…The deletion of MreB, or the inhibition of MreB polymerization using the drug A22, leads to spherical cells that are prone to lysis and have an altered cell wall structure (5,8,9). During elongation, we observed that MreB has a preference to localize to regions of small or even negative local Gaussian curvature.…”
Section: Introductionmentioning
confidence: 87%
“…5B). Localization of the over-produced membrane-bound GFPRodZ Ec revealed membrane invaginations and vesicles in the misshapen cells, strikingly reminiscent of the intracytoplasmic vesicles and membrane involutions observed in ⌬mreB cells (29). Both deletion and over-expression phenotypes show that cell morphogenesis in E. coli, as in C. crescentus, is severely impaired when RodZ function is altered.…”
Section: Conservation Of Rodz Function and Mreb-driven Localization Imentioning
confidence: 96%
“…5D), which was also observed in normal-sized cells (not shown). Deletion of MreB [in the presence of FtsZ over-production to support viability (16,29,30)] resulted in dispersion of GFP-RodZ Ec around the membrane (Fig. 5E).…”
Section: Conservation Of Rodz Function and Mreb-driven Localization Imentioning
confidence: 99%